Motives of Extremism Movements of Sudan Rapid Support Forces in the Sudan Conflict 2023 - Ardianti, Putri; Fidela, Mega Rahmanya; Setiawan, Zitto Zeppe; Suratiningsih, Dewi (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
The conflict between the Sudanese Armed Forces (SAF) and the Sudanese Rapid Support Forces (RSF) is a purely internal conflict because both parties want to fight for civilian leadership. Since Leader General Abdel Fattah Al-Burhan together with the Sudanese Rapid Support Forces (RSF) took over the power of al-Bashir's government. The struggle for power continues, marked by extremist movements from the Rapid Support Forces and the Sudanese Armed Forces Coup Movement. Since al-Burhan demonstrated the 2019 Constitutional agreement regarding political transition, extremist movements have been carried out by the Rapid Support Forces and in 2023 in the capital Khartoum to seize power from Abdel Fattah al-Burhan. This article aims to analyze 1) The influence of the Sudanese Rapid Support Force movement; 2) RSF's reasons for fighting SAF; 3) Impact on Sudanese State Security; 4) International laws violated in the RSF-SAF conflict. The method used in this paper is explanatory historical by collecting data on past events and using appropriate theories to explain the RSF-SAF conflict. Behind all the RSF's aggressive actions, Hemedti and his troops intended to overthrow Al-Burhan because he had betrayed the 2019 Constitution. As a result of the war between the RSF and SAF, Sudan turned into a country that contributed to immigrants and triggered a humanitarian crisis. The research contribution is: to examine the internal armed conflict in Sudan from a legal and political perspective, focusing particularly on the Rapid Support Forces (RSF) and their impact on state security, governance, and international legal norms